Permeation grouting mechanism of viscous time-varying fluid considering diffusion path - Wang, Hongbo; Dong, Lianglin; Zhang, Qingsong; Li, Zhipeng; Zhang, Peiyuan (Frontiers in Earth Science, 2023)
Due to the hidden nature of the grouting project, it has not been possible to get a clear picture of the slurry transport law, and most of the existing permeation grouting theories have ignored the tortuous characteristics of the pore channels of porous media. Based on the fractal theory of porous media and the equation of seepage motion of viscous time-varying Bingham fluid, a theoretical model of permeation grouting with viscous time-varying Bingham fluid is established, and viscosity tests are carried out for C-S slurry to obtain the time-varying equation of viscosity of C-S slurry. A set of permeation grouting simulation experiment device was designed, and the permeation grouting simulation experiment of C-S slurry was carried out to obtain the variation curve of grouting pressure with time under different injection media and different grouting rates. The results show that the grouting pressure considering the diffusion path of the slurry is 0.9-1.1 times of the experimental results, the grouting pressure obtained from the experimental is 0.7-1.2 times of the theoretical value considering the diffusion path, and the calculated value considering the diffusion path agrees well with the experimental value. The theoretical model can provide scientific guidance for field grouting construction.